2014
DOI: 10.4238/2014.december.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between MTP -493G>T polymorphism and non-alcoholic fatty liver disease risk: a meta-analysis

Li L1,
et al.

Abstract: ABSTRACT. Several studies have found that microsomal transfer protein (MTP) may be important in the development and progression of non-alcoholic fatty liver disease (NAFLD). In this meta-analysis, we evaluated the relationships between a common polymorphism (-493G>T, rs1800591 G>T) in the MTP gene and NAFLD risk. The PubMed, CISCOM, CINAHL, Web of Science, Google Scholar, EBSCO, Cochrane Library, and CBM databases were searched for relevant articles published before October 1, 2013 without any language restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…A functional SNP in the promoter region of MTTP (−493G/T) has been found to play an important role in the regulation of gene expression and influences the concentration of circulating LDL in the plasma of healthy individuals [10]. Zheng et al [11] and Li et al [12] conducted a meta-analysis and concluded that the MTTP -493G/T SNP is strongly associated with an increased risk of hepatic steatosis, which may contribute to the development of non-alcoholic fatty liver disease (NAFLD). Corroborating these data, Hsiao et al [13] found that MTTP SNPs, including MTTP -493G/T, could modulate lipid homeostasis and influence serum lipid levels and NAFLD risk.…”
Section: Introductionmentioning
confidence: 99%
“…A functional SNP in the promoter region of MTTP (−493G/T) has been found to play an important role in the regulation of gene expression and influences the concentration of circulating LDL in the plasma of healthy individuals [10]. Zheng et al [11] and Li et al [12] conducted a meta-analysis and concluded that the MTTP -493G/T SNP is strongly associated with an increased risk of hepatic steatosis, which may contribute to the development of non-alcoholic fatty liver disease (NAFLD). Corroborating these data, Hsiao et al [13] found that MTTP SNPs, including MTTP -493G/T, could modulate lipid homeostasis and influence serum lipid levels and NAFLD risk.…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed in enterocytes and hepatocytes, affects lipid absorption, and is related to NAFLD and diabetes . A meta‐analysis showed that an MTP polymorphism (genotype GG) was associated with NAFLD development by reducing the export of lipids to serum and triggering the accumulation of lipids inside hepatocytes . Moreover, this polymorphism was associated with an atherogenic lipid profile in non‐alcoholic steatohepatitis (NASH) .…”
Section: Discussionmentioning
confidence: 99%
“…25 A meta-analysis showed that an MTP polymorphism (genotype GG) was associated with NAFLD development by reducing the export of lipids to serum and triggering the accumulation of lipids inside hepatocytes. 26 Moreover, this polymorphism was associated with an atherogenic lipid profile in non-alcoholic steatohepatitis (NASH). 27 In NAFLD, SNPs related to lipid metabolism might play a more important role, whereas SNPs related to ethanol metabolism might be more relevant in ALD.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports several SNPs affecting its activity, with contrasting results. A recent meta-analysis confirmed that the promoter −493G > T polymorphism might be associated with NAFLD risk [70,71,72,73,74]. The minor allele (GG) has been linked to an increased postprandial lipid production and larger VLDL circulating levels.…”
Section: Genetic Variants Identified In Candidate Gene Studiesmentioning
confidence: 99%